Empowering the Local Economy Through Creative Product Innovation in Pematang Johar - Claudie Tiofanny; Phan Bao Giang; Muhammad Hafiz Abd.Rashid; Ridwan Nurdin; Nurma Sari; Ovie Esrani Panggabean (Eastasouth Institute, 2025)
Creative product innovation is vital for empowering local economies and improving MSME competitiveness, especially in rural areas. This community service in Pematang Johar Village aimed to strengthen creativity, innovation, and digital marketing among 42 participants, including MSME owners, youth, and women entrepreneurs. Through workshops and mentoring based on Service-Learning and Participatory Action Research (PAR), participants improved by over 50% in product design, packaging, and digital promotion. They created culturally inspired prototypes and formed the Pematang Johar Creative MSME Forum to ensure continued collaboration. The program shows that innovation enhances business competitiveness while promoting social inclusion and sustainability, contributing to SDGs 8 and 9 through inclusive economic growth and community-based innovation.